Pengembangan Media Pembelajaran Menggunakan Microsoft Powerpoint Pada Mata Pelajaran Ekonomi Sebagai Alternatif Belajar Mandiri Dimasa Pandemi - Huzain Jailani; Sri Kurnia Lestari; Muhamad Ali (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
This development was carried out to develop Economics Teaching Materials for Class X even semesters using Microsoft PowerPoint at MA Mu'allimat NWDI Pancor as an alternative for independent study during the pandemic that was valid and gave a positive response. The learning development model in this study uses the ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluation. However, in this study only up to the implementation stage. The research instrument used consisted of: (1) Media Validation Sheet, (2) Material Validation Sheet, (3) Teacher Assessment and Response Sheet, (4) Student Assessment and Response Sheet. The results showed that the feasibility level of learning media using Microsoft PowerPoint on economic subjects as an alternative for independent study during the pandemic was based on the assessment: 1) Material Experts obtained a total score of 68 in another word 80% which was included in the "Very Valid" category, 2) Media Experts obtained a total score of 46 0.0 in another word 92% which was included in the "Very Valid" category, 3) Economics Learning Practitioners (Teachers) give a total score of 111 in another word 88,8% which was included in the "Very Good" category. The students' response to this media when the trial was conducted on average showed a positive response by getting a percentage of 91.34% from the standard 61% as a whole. Thus the learning media using Microsoft PowerPoint is appropriate to be used as an alternative learning media in independent study, especially during the pandemic